Insight to drug delivery aspects for colorectal cancer - Gulbake, Arvind (World journal of gastroenterology : WJG, 2016)
Colorectal cancer （CRC） is the third most commoncancer diagnosed worldwide in human beings. Surgery,chemotherapy, radiotherapy and targeted therapies are the conventional four approaches which arecurrently used for the treatment of CRC. The sitespecific delivery of chemotherapeutics to their site ofaction would increase effectiveness with reducing sideeffects. Targeted oral drug delivery systems based onpolysaccharides are being investigated to target anddeliver chemotherapeutic and chemopreventive agentsdirectly to colon and rectum. Site-specific drug deliveryto colon increases its concentration at the target site,and thus requires a lower dose and hence abridged sideeffects. Some novel therapies are also briefly discussedin article such as receptor （epidermal growth factorreceptor, folate receptor, wheat germ agglutinin, VEGFreceptor, hyaluronic acid receptor） based targetingtherapy; colon targeted proapoptotic anticancer drugdelivery system, gene therapy. Even though goodtreatment options are available for CRC, the ultimatetherapeutic approach is to avert the incidence of CRC.It was also found that CRCs could be prevented by dietand nutrition such as calcium, vitamin D, curcumin,quercetin and fish oil supplements. Immunotherapyand vaccination are used nowadays which are showingbetter results against CRC.